PENDAMPINGAN UMKM (USAHA MIKRO KECIL DAN MENENGAH) MAKANAN TRADISIONAL REMPEYEK LEGENDARIS DI DESA TAWUN NGAWI - Hikmawati, Hanifah; Almasuri, Indah (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract The legendary Rempeyek still exists in the modern era. The crunchy, savory and delicious taste is very popular with the public. Because of this large number of enthusiasts, it is necessary to develop rempeyek as a traditional food. One of the UMKM that initiated rempeyek is in Tawun village. This growing UMKM has become a medium for preserving fast food in the form of rempeyek. The aim of this service is to provide assistance to UMKM Rempeyek Risky so that they can change the mindset of teenagers and the community in carrying out creativity. This service is carried out in 3 steps, namely preparation, implementation and reporting. The results obtained are that product marketing is very important in order to attract the attention and interest of the wider community in buying rempeyek products.